Efektivitas Gel Esktrak Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) terhadap Penyembuhan Ulser Pada Tikus Wistar - Mahardiani Dwi Astanti; Pujiana Endah Lestari; Iin Eliana Triwahyuni (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2022)
Ulcer is a lesion that is often found in the oral cavity that causes discomfort, pain, difficulty speaking and difficulty eating. Nowdays, herbal ingredients are widely used as alternative medicine choice besides drugs on the market. Pandan leaf contains flavonoids, alkaloids, saponins, and polyphenols which have antiinflammatory, antibacterial, and antioxidant abilities, allowing faster healing of ulcers. Purpose of this study was to determine the effect of pandanus leaf extract gel on healing ulcers and determine the most effective concentration in healing ulcers. This study used 25 Wistar rats divided into 5 groups, which were applied CMC-Na gel, aloclair gel, 25%, 50% dan 75% pandan wangi leaf extract gel. Each rat was made ulcer by heating the stopper amalgam on the bunsen fire for 30 seconds, then touching to the left buccal mucosa for 1 second, and waiting for 2x24 hours to form an ulcer. Giving the gel every morning and evening and measure the diameter of ulcers every day. This study showed healing time and decrease ulcer diameter pandanus leaf extract gel faster than negative control. The average recovery day was negative control for 9.8 days, positive control for 8 days, pandanus leaf extract gel concentration 25% for 8.6 days, concentration 50% for 8 days, and concentration 75% for 6.8 days. Pandan leaf extract gel accelerated ulcer healing and 75% concentration is the most effective.